PELATIHAN MANAJEMEN KESEHATAN DAN KESELAMATAN KERJA (K3) DI PUSKESMAS OESAPA - Adi Yermia Tobe; Rima Nindia Selan; Jefri S Bale; Daud Pulo Mangesa; Arifin Sanusi; Defmit B.N. Riwu; Jack C.A. Pah (Sekolah Vokasi Universitas Diponegoro, 2025)
Community Health Centers are the front guard in providing health services to the community, where the government has designated them as First Level Health Facilities (Level 1 Health Facilities) which are the reference for obtaining health insurance at the next level (Hospital). Therefore, community health centers must provide the best services and complete education, so that the goals of public health can be achieved. Occupational Health and Safety is an important element in protecting ourselves both from the service provider side (employees/staff) and from the service recipient side (patients/community). Occupational Health and Safety itself consists of several elements that must be understood, including: Occupational Diseases, Personal Protective Equipment, Psychology and Ergonomics, Comfort (Noise and Vibration), Dangers (Mechanical and Electrical) and ultimately can be intertwined in the Safety Management System and Occupational Health. All of these things have not been fully realized and applied in everyday life, even in health facilities. With this activity, it is hoped that the implementation of good Occupational Health and Safety will automatically increase the health figures of the community itself.